2021
DOI: 10.1111/jgh.15522
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence assists identifying malignant versus benign liver lesions using contrast‐enhanced ultrasound

Abstract: Background and Aim: This study aims to construct a strategy that uses assistance from artificial intelligence (AI) to assist radiologists in the identification of malignant versus benign focal liver lesions (FLLs) using contrast-enhanced ultrasound (CEUS). Methods: A training set (patients = 363) and a testing set (patients = 211) were collected from our institute. On four-phase CEUS images in the training set, a composite deep learning architecture was trained and tuned for differentiating malignant and benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Ultrasound (US) is an imaging tool inexpensive, non-aggressive, non based on X-rays suorces and so repeatable [ 30 40 ]. The possibility of injecting a contrast medium (Contrast-Enhanced Ultrasound (CEUS)) determines a technical evolution [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is an imaging tool inexpensive, non-aggressive, non based on X-rays suorces and so repeatable [ 30 40 ]. The possibility of injecting a contrast medium (Contrast-Enhanced Ultrasound (CEUS)) determines a technical evolution [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical variables, the predictive performance of the radiomics model in the study was similar to that of our linear and logistic models but was lower than that of the SVM, RF, and GBM models, which revealed that the optimal feature selection is important for building a precise model. Unlike the engineered features model, the DL model as a novel method for image classification has been widely used in liver cancers (37)(38)(39). A DL model based on CT and gadoxetic acid-enhanced magnetic resonance imaging (EOB-MRI) seemed efficient for predicting microvascular invasion in HCC (40).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the engineered features model, the DL model as a novel method for image classification has been widely used in liver cancers ( 37 39 ). A DL model based on CT and gadoxetic acid-enhanced magnetic resonance imaging (EOB-MRI) seemed efficient for predicting microvascular invasion in HCC ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The contrast agent spreads through the human body, emphasizing the vessel structure in the region of interest [22]. This technology leads to the highlighting of both large vessel flows, as well as of the microcirculation, being firstly implemented for hepatic tumor pathology, for abdominal emergencies and in order to recognize various tumor types [26][27][28][29][30][31][32][33][34][35][36]. The microbubbles of the contrast agent produce harmonic echoes, which are detected by the transducer.…”
Section: Diagnostic Tools Ultrasoundmentioning
confidence: 99%